Bowel damage and disability in Crohn's disease: a prospective study in a tertiary referral centre of the Lémann Index and Inflammatory Bowel Disease Disability Index. Issue 9 (27th March 2020) - Lauriot dit Prevost, Clémentine; Azahaf, Mustapha; Nachury, Maria; Branche, Julien; Gerard, Romain; Wils, Pauline; Lambin, Thomas; Desreumaux, Pierre; Ernst, Olivier; Pariente, Benjamin
Summary: Background: The notion of Crohn's disease (CD) as a chronic, progressive and disabling condition has led to the development of new indexes: the Lémann Index measuring cumulative bowel damage and the Inflammatory Bowel Disease (IBD) Disability Index, assessing functional disability. Aims: To measure the Lémann Index and the IBD Disability Index in a large prospective cohort of CD patients and to assess the correlation between these two indexes. Methods: We performed a prospective study in a tertiary referral centre including all consecutive CD outpatients. We assessed the Lémann Index and the IBD Disability Index questionnaire in all patients. Results: One hundred and thirty CD patients were consecutively included. The mean Lémann Index (±SD) was 11.9 ± 14.1 and ranged from 0 to 72.5 points. Factors associated with a high bowel damage score were: disease duration, anal location, previous intestinal resection, clinical and biological disease activity, exposure to immunosuppressants, and exposure to anti‐TNF ( P < 0.005). Among patients exposed to anti‐TNF, the Lémann Index was lower in those who were exposed in the first 2 years of their disease ( P = 0.015). The mean IBD Disability Index was 28.8 ± 6.3 and ranged from 0 to 71 points. The factors associated with high disability score were: female gender, anal location, extra digestive manifestations, clinical and biological disease activity and exposure to anti‐TNF ( P < 0.005). No correlation was observed between the Lémann Index and IBD Disability Index ( P = 0.15). Conclusions: This is the first study to prospectively evaluate the Lémann Index and the IBD Disability Index in a large cohort of CD patients in a tertiary centre. Early introduction of anti‐TNF treatment was associated with lower bowel damage scores, and no correlation was observed between the Lémann Index and the IBD Disability Index. Further dedicated prospective studies are necessary to confirm these results.